Predicting physical activity intention and behaviour using achievement goal theory: A person-centred analysis. (March 2016) - Wang, John C.K.; Morin, Alexandre J.S.; Liu, W.C.; Chian, L.K.
Abstract: The purpose of the current study was to identify the 2 × 2 achievement goals profiles at the intraindividual level using a latent profile analyses (LPA) approach while controlling for the nesting of students within classroom. Additional analyses involving the direct inclusion of predictors and outcomes to the final latent profile solution were also used to examine the relationships between the latent profiles and perceived motivational climate, intention to be physically active and physical activity participation. A sample of 1810 school children aged 14–19 years drawn from 79 classes in 13 Singaporean schools took part in the study. Using the latent profile analysis, four distinct motivational profiles could be identified. The results from multinomial logistic regressions showed that profile membership was significantly predicted by perceptions of mastery and performance climate. Finally, the results showed that the four profiles differed significantly in terms of intention to be physically active and physical activity participation. Highlights: Identified 2 × 2 achievement goal profiles using latent profile analysis. Employed multinomial logistic regression to examine profiles related to motivational climate and outcomes. Profile membership was significantly predicted by perceptions of mastery and performance climate. Four profiles differed significantly in terms of intention and physical activity participation.